2020
DOI: 10.3390/ijms21020387
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Beta Neutralization Attenuates Traumatic Brain Injury-Induced Microglia Activation and Neuronal Changes in the Globus Pallidus

Abstract: Traumatic brain injury (TBI) increases the risk of delayed neurodegenerative processes, including Parkinson’s disease (PD). Interleukin-1beta (IL-1β), a key pro-inflammatory cytokine, may promote secondary injury development after TBI. Conversely, neutralizing IL-1β was found to improve functional recovery following experimental TBI. However, the mechanisms underlying the behavioral improvements observed by IL-1β neutralization are still poorly understood. The present study investigated the role of IL-1β on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In the cortex, the microglia/macrophage response was limited in distribution indicating a more contained inflammatory response. As a result of IL1β involvement in microglia activation and proliferation as well as monocyte recruitment, our observed decreased microglia/macrophage density in the perilesional cortex and CA1 may be a result of CoSyn-mediated reduction in IL1β expression (Basu et al, 2002;Ozen et al, 2020). As the tissue-resident macrophage, microglia are key players in the inflammatory process following brain injury resulting in regenerative, phagocytic, and pro-/anti-inflammatory phenotypes (Xu et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the cortex, the microglia/macrophage response was limited in distribution indicating a more contained inflammatory response. As a result of IL1β involvement in microglia activation and proliferation as well as monocyte recruitment, our observed decreased microglia/macrophage density in the perilesional cortex and CA1 may be a result of CoSyn-mediated reduction in IL1β expression (Basu et al, 2002;Ozen et al, 2020). As the tissue-resident macrophage, microglia are key players in the inflammatory process following brain injury resulting in regenerative, phagocytic, and pro-/anti-inflammatory phenotypes (Xu et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…Interleukin-1-beta (IL1β) is an early inflammatory cytokine that is restored to sham-levels within 1 week following injury and is involved in the secondary injury cascade (Dalgard et al, 2012 ; Lagraoui et al, 2012 ; Taib et al, 2017 ). IL1β neutralization studies demonstrated the causal role of increased IL1β levels in driving neuronal loss (Ozen et al, 2020 ), circulating macrophage recruitment (Basu et al, 2002 ), injury-induced oligodendrocyte damage (Flygt et al, 2018 ), and microglial activation and proliferation following TBI (Ozen et al, 2020 ). Collectively, these data suggest reduced IL1β is beneficial following experimental TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of IL-1β have been correlated with worsening of infarct severity ( Yamasaki et al., 1995 ), and genetic deletion of IL-1β and IL-1R1 have resulted in positive or neuroprotective outcomes in murine stroke model ( Boutin et al., 2001 ; Lazovic et al., 2005 ). In TBI, untoward effects of IL-1β are supported by preclinical findings ( Clausen et al., 2011 ; Ozen et al., 2020 ). In congruence, administration of rHuIL-1Ra in preclinical TBI models and to patients have shown favourable effects such as reduced neuroinflammation and improved cognition ( Helmy et al., 2014 ; Newell et al., 2018 ).…”
Section: Discussionmentioning
confidence: 82%
“…In terms of the complexity of cortico-ponto-cerebellar pathways, one possibility could be the involvement of other brain regions, such as pontine nuclei and basal ganglia converging on different subset of Purkinje cells with altered synaptic input and connectivity patterns in the damaged cerebellum. On the other hand, cFPI also results in striatal pathology, in particular in the globus pallidus, which may also have influenced the beam walk test [ 37 ]. However, while not specific for cerebellar function this test remains sensitive in the assessment of cerebellar pathology [ 28 ].…”
Section: Discussionmentioning
confidence: 99%